The effect of perindopril, a new angiotensin converting enzyme inhibitor on the hormonal response to brisk exercise in healthy subjects - Klug, Eric, Quinton (My University, 1994)
Cardiovascular drugs have varying effects on haemodynamic, metabolic, and hormonal responses to exercise. Angiotensin converting enzyme inhibitors (ACEI) have been used for the treatment of systemic hypertension, left ventricular dysfunction with or without congestive heart failure, and increasingly, for occlusive coronary artery disease and its complications..
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, for the Degree of Master of Medicine. Johannesburg 1994.
Keywords: Perindopril; Angiotensins; Enzyme Inhibitors